Effect of Coal Smoke Pollution on the Biomass and Chlorophyll Pigments of Brassica juncea - Saquib, Mohammad (Ecoprint: An International Journal of Ecology, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> The effect of coal smoke pollution on the biomass and chlorophyll pigments of Brassica juncea were studied at 0.5, 2, 4, 6 and 20 km distance leeward from a thermal power plant complex. The root, shoot and total biomass and chlorophyll a, chlorophyll b and total chlorophyll were significantly reduced up to a distance of 4 km from the source of pollution. The data indicates that the degree of response increased with decreasing distance from the source of pollution in comparison to the reference site ‘c' situated at 20 km. Biomass and chlorophyll pigments showed a significant and positive relationship with the distance from the source. Key words: Air pollution, Brassica juncea, biomass, chlorophyll. doi: 10.3126/eco.v15i0.1935 ECOPRINT 15: 1-6, 2008